Bibliometric Analysis of Research of Cash Waqf Using Vosviewer - Nil Firdaus; Rizal Rizal (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: Cash Waqf becomes an important issue as a solution to improve the welfare of today’s’ societies. The various studies have been conducted both theoretically and empirically to produce findings in the cash waqf study. This study aims to map writings related to cash waqf.Design/Method/Approach: This research is a quantitative descriptive research through mapping research on cash waqf.Findings: The results of the study showed that writing using the search for cash waqf titles indexed Scopus is as many as 43 documents. While the title search with the word Cash Waqf on Google Scholar as many as 529 documents. Scopus's most-cited indexed journal usurious piety: The Cash Waqf Controversy in the Ottoman Empire was written by J. Mandaville for 79 citations. While on Google Scholar writing with the title Cash waqf and its influence on poverty alleviation program in Indonesia by M Nur al-Arif as many as 451 citations.Originality/Values: The main contribution to this study is to find out the extend of research on cash waqf and the rarely studied themes about cash waqf.